LcrG, a secreted protein involved in negative regulation of the low-calcium response in Yersinia pestis. - Skryzpek, E (1993)
The purpose of this study was to define the function of LcrG, the product of the first gene in the lcrGVHyopBD operon of the low-Ca(2+)-response (LCR) virulence plasmid of Yersinia pestis. We created a Y. pestis strain having an in-frame deletion in lcrG. This nonpolar mutant had an abnormal LCR growth phenotype: it was unable to grow at 37 degrees C in the presence of 2.5 mM Ca2+ ("Ca2+ blind") but was able to grow at 37 degrees C when 18 mM ATP was present. At 37 degrees C it failed to downregulate the expression and secretion of its truncated product (LcrG), V antigen, and YopM. All of these mutant properties were complemented by plasmids carrying normal lcrG. However, a nonpolar lcrE mutation and an lcrH mutation (both also causing a Ca(2+)-blind phenotype) were not complemented in this way. The Y. pestis parent strain expressed LcrG at 37 degrees C in the presence and absence of Ca2+ and transported it to the medium when Ca2+ was absent. We identified two LCR-regulated loci, lcrD and yscDEF, required for this transport. Complementation analysis of the Y. pestis lcrR strain previously shown to lack the expression of LcrG showed that the loss of LcrG but not of LcrR caused the Ca(2+)-blind phenotype of that mutant. Taken together, the results show that LcrG is a negative regulator of the LCR, perhaps functioning in Ca2+ sensing along with LcrE.